DAAFA’IYATU ATTA’LIIM WA’ALAAQOTUHAA BISTII’AABI QOWAAIDI ALLUGAH AL’AROBIYYAH BIMA’HAD SABIILIL ALMUKMININ - Arbonas Lubis; Rozaanah Rozaanah; Qurrata Ayuni Br Ginting (Universitas Islam Negeri Mataram, 2022)
One of the general principles of teaching Arabic grammar is that the learner must feel the need for the rules and feel their usefulness, and the need for internal motivation. Research question: Is there a relationship between learning motivation and comprehension of Arabic grammar among eleventh grade students in the secondary stage at Sabeel Al-Muminin Institute in Najai? Its aim is to find out the relationship between learning motivation and comprehension of Arabic grammar among eleventh grade students in the secondary stage at Sabeel Al-Muminin Institute in Najai. The method used is the quantitative method of the relational type, and the method of analyzing the data used is a statistical method with the symbol Product Moment. As a result of the research, there is a relationship between learning motivation and comprehension of Arabic grammar among eleventh grade students in secondary school at Sabeel Al-Muminin Institute in Nagai, with a correlation coefficient value of 0.808, and the relationship is strong in the same direction. The reciprocal hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. In conclusion, there is a strong relationship between learning motivation and comprehension of rules.